Generating brand awareness and customer relations with the most suitable marketing strategy and tools in Andika broker - Arnold Joseph Pakan (Universitas Wiralodra, 2023)
The development of competition in businesses nowadays is more than just competition within the quality of their products or services. The competition starts from how they promote their names and brands through social media to increase market awareness towards the brand through several types of strategy. Nevertheless, the promotion methods in a business-to-business company are quite different compared to a business-to-consumer company. The study focuses on determining the most suitable marketing strategy to increase brand awareness and generate customer loyalty in a B2B company. In this case, it will be conducted in Andika Broker, which operates in the insurance line of business. Data were collected from 70 representatives of 14 corporate clients of Andika Broker around Jakarta through in-depth interviews with the person in charge, observation during the operation, and online surveys to the target respondents. The findings indicate that even in a business-to-business market, it is essential to increase brand awareness outside the HR Division and maintain relationships with the person in charge through a well-organized customer loyalty program. Understanding the appropriate marketing strategy and tools needed in a business-to-business market is of great value for academia and the industry.